2006
DOI: 10.1001/archneur.63.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Human Growth Hormone–Related Iatrogenic Creutzfeldt-Jakob Disease With Abnormal Imaging

Abstract: Background: Although more than 160 cases of iatrogenic Creutzfeldt-Jakob disease (iCJD) from human growth hormone (hGH) treatment have been documented, to our knowledge abnormal cerebellar findings on magnetic resonance imaging (MRI) have not been reported. Objective: To report a case of hGH-related iCJD with abnormal cerebellar MRI findings on fluid-attenuated inversion recovery (FLAIR) and diffusion-weighted MRI (DWI). Design: Case report. Setting: Outpatient neurology clinic at a university medical center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…Poon et al [29] reported one case with the Brownell-Oppenheimer (cerebellar) variant of CJD with clear DWI (and weaker FLAIR) cerebellar hyperintensity. Lewis et al [30] reported similar findings in one case of hGH-related iCJD, but two other cases revealed no cerebellar MRI findings, despite clinical cerebellar signs. In fact, this paradoxical pattern of negative cerebellar MRI with proven neuropathological degeneration postmortem is common in the CJD literature [31,32].…”
Section: Discussionmentioning
confidence: 69%
“…Poon et al [29] reported one case with the Brownell-Oppenheimer (cerebellar) variant of CJD with clear DWI (and weaker FLAIR) cerebellar hyperintensity. Lewis et al [30] reported similar findings in one case of hGH-related iCJD, but two other cases revealed no cerebellar MRI findings, despite clinical cerebellar signs. In fact, this paradoxical pattern of negative cerebellar MRI with proven neuropathological degeneration postmortem is common in the CJD literature [31,32].…”
Section: Discussionmentioning
confidence: 69%
“…CJD occurs in new-variant and classical (sporadic and iatrogenic) forms. Iatrogenic CJD followed administration of cadaveric human pituitary hormones (192,193), dural graft transplants (194), corneal transplants (195), and the use of contaminated neurosurgical instruments (196).…”
Section: Creutzfeldt-jakob Disease (Prion Disease)mentioning
confidence: 99%
“…Lai /Tseng Neuroepidemiology 2009;33:247-253 248 mones [6][7][8] , dural graft transplants [9] , use of dura mater in radiographic embolization procedures [10] , corneal transplants [11,12] , liver transplants [13] and the use of contaminated neurosurgical instruments or stereotactic depth electrodes [14] . An international study of the epidemiological characteristics of CJD, which included national registries in France, Germany, Italy, The Netherlands, Slovakia, UK, Australia, Austria, Canada, Spain and Switzerland, showed that the overall annual mortality rate between 1999 and 2002 was 1.67/million for all cases and 1.39/million for sporadic CJD [15] .…”
mentioning
confidence: 99%